Latency of breast cancer stigma during survivorship and its influencing factors: A qualitative study - Melhem, Samar J.; Nabhani-Gebara, Shereen; Kayyali, Reem (Frontiers in Oncology, 2023)
Introduction Breast cancer diagnosis and treatment have been shown in studies to have a negative impact on patients' physical, psychological, and social well-being, as well as overall quality of life. Psychologically, it's linked to sadness, anxiety, and demoralisation. Stigma contributes to the hidden burden of breast cancer as a chronic illness. Research on the elements that breast cancer survivors encounter as influences on stigma associated to the disease is lacking. Based on the lived experiences of breast cancer survivors, this study sought to investigate the factors that lead to the manifestations of both self- and public breast cancer stigma. Methods Individual semi-structured interviews with 24 patients diagnosed with breast cancer were performed, followed by five focus groups with 25 patients diagnosed with breast cancer. Interviews were verbatim transcribed and analysed using thematic framework analysis. Results Two major themes have emerged from the data: a) Breast cancer stigma among breast cancer survivors, highlighting the various manifestations of stigma and the variables that influence them; including disease-related factors, patients' views of cancer, public perceptions of breast cancer, family and interpersonal dynamics, and b) Stigma resilience and empowerment, emphasising the necessity of sociocultural transformation and coping strategies to preserve resilience. Conclusions To improve the well-being of breast cancer survivors, practitioners and health policymakers should be aware of the breast cancer stigma that underpins patients' emotional and behavioural outlooks and its potential consequences on patients' quality of life. They need to develop interventions to address the different stages of cancer stigma taking into consideration sociocultural influences, norms, and beliefs.